2012
DOI: 10.2147/ijn.s28344
|View full text |Cite
|
Sign up to set email alerts
|

Cell-delivered magnetic nanoparticles caused hyperthermia-mediated increased survival in a murine pancreatic cancer model

Abstract: Using magnetic nanoparticles to absorb alternating magnetic field energy as a method of generating localized hyperthermia has been shown to be a potential cancer treatment. This report demonstrates a system that uses tumor homing cells to actively carry iron/iron oxide nanoparticles into tumor tissue for alternating magnetic field treatment. Paramagnetic iron/ iron oxide nanoparticles were synthesized and loaded into RAW264.7 cells (mouse monocyte/ macrophage-like cells), which have been shown to be tumor homi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 58 publications
1
68
0
1
Order By: Relevance
“…In another study, three cycles of hyperthermia using targeted iron oxide nanoparticles increased the survival by 31% in mice with pancreatic cancer. 23 Our results suggest that the efficacy of Dex-LSMO nanoparticles-mediated hyperthermia is comparable to that reported for iron oxide nanoparticles.…”
Section: Discussionsupporting
confidence: 78%
“…In another study, three cycles of hyperthermia using targeted iron oxide nanoparticles increased the survival by 31% in mice with pancreatic cancer. 23 Our results suggest that the efficacy of Dex-LSMO nanoparticles-mediated hyperthermia is comparable to that reported for iron oxide nanoparticles.…”
Section: Discussionsupporting
confidence: 78%
“…17,[38][39][40] Direct intratumoral injections of MNPs followed by induction heating has shown some benefit in controlling tumor growth. 38,[41][42][43][44][45][46][47][48][49] Direct intratumoral injection was used in the first MNP hyperthermia clinical trial treating a prostate cancer using a 100 kHz machine designed for human patients, 50 and later in human glioma trials 51,52 which demonstrated safety and some benefit. Heating was obtained, but due to inhomogeneous MNP distribution, complete tumor eradication was not possible.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the absence of any immune response in our mouse model may be significant. A recent study by Basel et al 45 evaluated mouse monocyte/macrophage-like cells as iron carriers that migrate toward disseminated peritoneal pancreatic cancer cells after intraperitoneal injection. They showed an increase in survival time in the AMF-treated mice compared to controls, using a combination of cell labeling and AMF characteristics that resulted in an overall tumor heating of 4°C -similar to that observed in this study.…”
Section: Discussionmentioning
confidence: 99%